Standard procedures for care and management of children with reactive syphilis at Kardinah Regional Hospital, Tegal City, 2025 - Ridlo, Ahmad; Khoeroh, Himatul (Indonesian Journal of Health Science, 2026)
Background: Syphilis or king lion disease is a sexually transmitted infection (STI) caused by the Treponema Pallidium bacteria. This disease begins with a painless sore, usually found on the genitals, rectum or mouth. Based on data from the Central Java Department, there were 368 cases of syphilis throughout 2024, Tegal Regency, which is a city in Central Java, contributed 4 cases of syphilis, 2 of which were in pregnant women who underwent examination at Kardinah Regional Hospital. Objective: The purpose of this study was to provide care and management of childbirth cases with reactive syphilis at Kardinah Regional Hospital according to standards. Research Method: The method in this study used a descriptive qualitative method with a case study approach through subjective, objective, assessment and planning elements. Data were collected through observation, in-depth interviews, physical and supporting examinations, KIA books, and medical records. The main informants were determined by purposive sampling technique, namely mothers giving birth with reactive syphilis who were giving birth at Kardinah Regional Hospital, while additional informants were husbands, families, midwives in the VK room and obstetricians. Results: Based on the care and management of childbirth with reactive syphilis cases, there was no significant difference in the assistance of normal vaginal delivery provided there were no vaginal lesions and scabs on the body or canker sores in the mouth or lips.